Technology, production and partnership innovation in Uganda - Musaazi, M (Refugee Studies Centre, University of Oxford, 2014)
Since 2007 a partnership between UNHCR, the Government of Uganda and ‘MakaPads’ inventor Moses Musaazi has helped provide affordable sanitary pads for thousands of refugee girls and women while substantially reducing UNHCR’s expenditure on these essential items.